THE ROLE OF DIGITAL MARKETING AND LOGISTICS IN THE OPTIMIZATION OF BUSINESS PROCESSES OF AGRICULTURAL ENTERPRISES - Todoruk, Sergy; Kyfyak, Viktoria; Kyfyak, Oleksandr; Kindzerskyy, Vitaliy; Kovbas, Halyna; Finagina, Olesya (My University, 2023)
The scientific paper analyzes the influence of digital marketing and logistics on the optimization of business processes of agricultural enterprises. In the article, the authors used special and general scientific research methods: induction and deduction, scientific abstraction and systematization, analysis and synthesis, abstract-logical generalization, dialectical method and graphic method. A scheme for the analysis of business processes of agricultural enterprises in the context of the development of digital marketing and logistics is proposed. The main areas that will contribute to the optimization of business processes of agricultural enterprises have been determined. It is substantiated that the balanced organization and rationalization of business processes are important for achieving the effectiveness and efficiency of the activities of enterprises in the field of agriculture, and digital marketing and logistics play an important role in the optimization of business processes of agricultural enterprises, ensuring effective management of resources, increasing productivity and competitiveness.
Keywords: business processes; digital marketing; logistics; agricultural enterprises; optimization; management; clusters; innovation; education; personnel; post-war reconstruction; personnel management; financial management